A New Efficient Credit Scoring Model For Personal Loan Using Data Mining Technique For Sustainability Management - Rabihah Md Sum; Waidah Ismail; Nurul Fathihin Mohd Noor Shah; Zul Hilmi Abdullah (UMT, 2024)
Indexed by Scopus/ERA/MyCite